Mechanisms of mitophagy and oxidative stress in cerebral ischemia–reperfusion, vascular dementia, and Alzheimer’s disease - Lyu, Yujie; Meng, Zhipeng; Hu, Yunyun; Jiang, Bing; Yang, Jiao; Chen, Yiqin; Zhou, Jun; Li, Mingcheng; Wang, Huping (Frontiers in Molecular Neuroscience, 2024)
Neurological diseases have consistently represented a significant challenge in both clinical treatment and scientific research. As research has progressed, the significance of mitochondria in the pathogenesis and progression of neurological diseases has become increasingly prominent. Mitochondria serve not only as a source of energy, but also as regulators of cellular growth and death. Both oxidative stress and mitophagy are intimately associated with mitochondria, and there is mounting evidence that mitophagy and oxidative stress exert a pivotal regulatory influence on the pathogenesis of neurological diseases. In recent years, there has been a notable rise in the prevalence of cerebral ischemia/reperfusion injury (CI/RI), vascular dementia (VaD), and Alzheimer’s disease (AD), which collectively represent a significant public health concern. Reduced levels of mitophagy have been observed in CI/RI, VaD and AD. The improvement of associated pathology has been demonstrated through the increase of mitophagy levels. CI/RI results in cerebral tissue ischemia and hypoxia, which causes oxidative stress, disruption of the blood–brain barrier (BBB) and damage to the cerebral vasculature. The BBB disruption and cerebral vascular injury may induce or exacerbate VaD to some extent. In addition, inadequate cerebral perfusion due to vascular injury or altered function may exacerbate the accumulation of amyloid β (Aβ) thereby contributing to or exacerbating AD pathology. Intravenous tissue plasminogen activator (tPA; alteplase) and endovascular thrombectomy are effective treatments for stroke. However, there is a narrow window of opportunity for the administration of tPA and thrombectomy, which results in a markedly elevated incidence of disability among patients with CI/RI. It is regrettable that there are currently no there are still no specific drugs for VaD and AD. Despite the availability of the U.S. Food and Drug Administration (FDA)-approved clinical first-line drugs for AD, including memantine, donepezil hydrochloride, and galantamine, these agents do not fundamentally block the pathological process of AD. In this paper, we undertake a review of the mechanisms of mitophagy and oxidative stress in neurological disorders, a summary of the clinical trials conducted in recent years, and a proposal for a new strategy for targeted treatment of neurological disorders based on both mitophagy and oxidative stress.